Supply chain sustainability and resilience: The case of apparel industry in Bangladesh - Chowdhury, Md. Maruf Hossan (Curtin University, 2014)
This study develops a model of supply chain (SC) resilience and sustainability based on stakeholder theory and resource based view. The research uses mixed method research design where both qualitative (field study) and quantitative (large-scale survey) methods are employed. The results reveal that resilience has negative impact on SC vulnerability and positive impact on sustainability. Resilience also mediates the relationship between SC risk management and vulnerability. The findings have both theoretical and practical significance.